Daclatasvir and asunaprevir treatment in patients with severe liver fibrosis by hepatitis C virus genotype 1b infection: Real‐world data. Issue 11 (10th October 2017) - Ishigami, Masatoshi; Hayashi, Kazuhiko; Honda, Takashi; Kuzuya, Teiji; Ishizu, Yoji; Ishikawa, Tetsuya; Nakano, Isao; Urano, Fumihiro; Kumada, Takashi; Yoshioka, Kentaro; Goto, Hidemi; Hirooka, Yoshiki
Abstract: Background and Aim: In this study, we investigated the real‐world data of the first approved interferon‐free regimen in Japan: daclatasvir and asunaprevir in chronic hepatitis C patients with severe fibrosis. Methods: Among 924 patients registered in our multicenter study, 535 patients were defined as having severe fibrosis with Fib‐4 index ≧ 3.25 and were included in this study. We investigated antiviral effect and factors associated with sustained viral response 12 (SVR12), and the additional effects on serum α‐fetoprotein and albumin levels by eradicating virus in patients who attained SVR were investigated. In statistical analysis, P  < 0.05 was considered as significant levels. Results: Antiviral effect was lower in patients with severe fibrosis at 8 and 12 weeks after start of the treatment (96.3%, 97.1% with severe fibrosis vs 99.5%, 99.2% without severe fibrosis, P  = 0.002 and P  = 0.036, respectively), and more early relapse (SVR4; 90.4% with severe fibrosis vs 95.4% without fibrosis, P  = 0.008) was seen in patients with severe fibrosis; however, there were no differences in SVR12 and SVR24. In the safety profiles, discontinuation rate due to liver injury (2.8% with severe fibrosis vs 3.3% without severe fibrosis) or other causes of discontinuation was not different between two groups. Serum α‐fetoprotein significantly decreased, and serum albumin levels significantly increased as early as 4 weeks after the start of treatment. Conclusion: Although the antiviral effect was slightly lower in patients with severe fibrosis compared with those without, treatment with daclatasvir and asunaprevir is basically an effective and well‐tolerable treatment in these populations.